'I don't want to be a teacher': a collaborative autoethnographic inquiry into the construction of university ELT instructors' professional identity. (18th August 2022) - Intansari Meilani, Rini; Kurniawati, Dewi; Nurfaidah, Sitti
ABSTRACT: Believing teachers as agents who actively make meaning about their professional identities, we depict the construction of our identity as three mid-career female English language teachers. Anchored by collaborative autoethnography (CAE) and arts-based educational research (ABER) approaches, we explored and reflected on our lived critical incidences significant to our professional learning and identity development. By expressing and reflecting upon literary and visual data that we concurrently collected and iteratively analysed, we are becoming more aware of how our identity as ELT instructors has been historical, socio-culturally, and institutionally shaped and reshaped. Our collaborative work has helped us to forecast our future professional development paths and inspired us to extend the collaborative research that promotes community capacity building among us and the wider academic community.